Induction of High Levels of Specific Humoral and Cellular Responses to SARS-CoV-2 After the Administration of Covid-19 mRNA Vaccines Requires Several Days - Gil-Manso, Sergio; Carbonell, Diego; López-Fernández, Luis; Miguens, Iria; Alonso, Roberto; Buño, Ismael; Muñoz, Patricia; Ochando, Jordi; Pion, Marjorie; Correa-Rocha, Rafael (Frontiers in Immunology, 2021)
Objectives. In the context of the Covid-19 pandemic, the fast development of vaccines with efficacy of around 95% preventing Covid-19 illness provides a unique opportunity to reduce the mortality associated with the pandemic. However, in the absence of efficacious prophylactic medications and few treatments for this infection, the induction of a fast and robust protective immunity is required for effective disease control, not only to prevent the disease but also the infection and shedding/transmission. The objective of our study was to analyze the level of specific humoral and cellular T-cell responses against the spike protein of SARS-CoV-2 induced by two mRNA-based vaccines (BNT162b2 and mRNA-1273), but also how long it takes after vaccination to induce these protective humoral and cellular immune responses. Methods. We studied in 40 healthy (not previously infected) volunteers vaccinated with BNT162b2 or mRNA-1273 vaccines the presence of spike-specific IgG antibodies and SARS-CoV-2-specific T cells at 3, 7 and 14 days after receiving the second dose of the vaccine. The specific T-cell response was analyzed stimulating fresh whole blood from vaccinated volunteers with SARS-CoV-2 peptides and measuring the release of cytokines secreted by T cells in response to SARS-CoV-2 stimulation. Results. Our results indicate that the immunization capacity of both vaccines is comparable. However, although both BNT162b2 and mRNA-1273 vaccines can induce early B-cell and T-cell responses, these vaccine-mediated immune responses do not reach their maximum values until 14 days after completing the vaccination schedule. Conclusion. This refractory period in the induction of specific immunity observed after completing the vaccination could constitute a window of higher infection risk, which could explain some emerging cases of SARS-CoV-2 infection in vaccinated people.